A secure data routing schema for WSN using Elliptic Curve Cryptography and homomorphic encryption - Mohamed Elhoseny; Hamdy Elminir; Alaa Riad; Xiaohui Yuan (Journal of King Saud University: Computer and Information Sciences)
Despite the great efforts to secure wireless sensor network (WSN), the dynamic nature and the limited resources of sensor nodes make searching for a secure and optimal network structure an open challenge. In this paper, we propose a novel encryption schema based on Elliptic Curve Cryptography (ECC) and homomorphic encryption to secure data transmission in WSN. The proposed encryption schema is built upon GASONeC algorithm (Elhoseny et al., 2014) that uses genetic algorithm to build the optimum network structure in the form of clusters. ECC is used to exchange public and private keys due to its ability to provide high security with small key size. The proposed encryption key is 176-bit and is produced by combining the ECC key, node identification number, and distance to its cluster head (CH). To reduce energy consumption of CH, homomorphic encryption is used to allow CH to aggregate the encrypted data without having to decrypt them. We demonstrated that the proposed method is capable to work with different sensing environments that need to capture text data as well as images. Compared with the state-of-the-art methods, our experimental results demonstrated that our proposed method greatly improve the network performance in terms of lifetime, communication overhead, memory requirements, and energy consumption.